Longitudinal Associations of Cigarette Prices With Smoking Cessation: The Coronary Artery Risk Development in Young Adults Study. Issue 5 (25th May 2018) - Mayne, Stephanie L; Gordon-Larsen, Penny; Schreiner, Pamela J; Widome, Rachel; Jacobs, David R; Kershaw, Kiarri N
Abstract: Introduction: Few studies have used longitudinal cohort data to examine associations of cigarette prices with smoking cessation or whether price sensitivity varies by income or education. This study examines these associations in a multicenter US cohort and explores whether associations vary by education and income. Methods: Longitudinal data from baseline daily cigarette smokers aged 18–30 years in the Coronary Artery Risk Development in Young Adults study were linked to inflation-adjusted cigarette carton prices from the Council for Community and Economic Research Cost of Living Index based on residential address at baseline and in years 7, 10, and 15 (1985–2001). Multivariable Cox models estimated hazard ratios (HRs) of first (any) smoking cessation and sustained smoking cessation (no relapse) associated with each 1 increase in time-dependent cigarette price over 15 years of follow-up. Models were adjusted for sociodemographic, health-related, and policy covariates. We assessed effect modification by education and household income. Results: Among 1489 participants, a 1.00 higher cigarette carton price was associated with a 16% higher likelihood of first smoking cessation (HR = 1.16, 95% CI = 1.11 to 1.21) and an 8% higher likelihood of sustained smoking cessation (HR = 1.08, 95% CI = 1.02 to 1.14). Associations were strongest among participants with lower income for first cessation, and among those with higher income for sustained cessation. Associations were strongest for participants with less than a high school degree for both outcomes. Conclusions: Results suggest higher cigarette prices promote smoking cessation among young to middle-aged adults, and that price sensitivity may differ by socioeconomic status. Implications: Few studies have examined longitudinal associations of cigarette prices with smoking cessation, and findings are mixed on whether price sensitivity varies by education or income. In a cohort of US adult daily smokers, cigarette prices were associated with greater likelihood of both a first cessation and sustained cessation. Price associations with first cessation were stronger among low-income smokers, but associations with sustained cessation were stronger among high-income smokers. Results suggest that although higher cigarette prices may promote short-term smoking cessation among smokers at all income levels, additional supports may be needed to facilitate sustained smoking cessation among low-income smokers.